Penerapan Algoritma String Matching dan Regular Expression pada Aplikasi Kamus Besar Bahasa Indonesia (KBBI) - Bintang, Jasmine Mutiara; Ashshidiq, Muhammad Faisal; Dzakwan, Hilal Fakhri (Puslitbang Sinergis Asa Professional, 2023)
The Kamus Besar Bahasa Indonesia (KBBI) application is a software or application that allows users to access and search for the meaning of a single word in Indonesian along with its spelling. Indonesian has a complex morphological structure, where words can change form through affixation (addition of prefixes or suffixes), reduplication, or internal changes that create many dialectal variations and spelling variations that can affect word forms and writing patterns. This causes a variety of words that are similar but different in writing. On the other hand, that the Indonesian Dictionary application needs speed and accuracy of word searches then the program makes adjustments to those in the dictionary. Therefore, researchers analyze based on the data that has been obtained by the KBBI application using string matching (brute force) and regular expression algorithms. Researchers hope that the algorithms that have been analyzed can help solve problems in the KBBI application in conducting word searches to find the meaning of spelling funds.